Pemberdayaan Masyarakat Kota Dibidang Ekonomi Melalui UMKM Ladu Arai Pinang Di Lubuk Buaya Kota Padang - Salsabila Fatine (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
Community empowerment activities are a conscious and planned effort carried out by the community that aims to empower people, from those who cannot become capable by utilizing the potential in the community. This community empowerment activity in the economic field is carried out because it is based on problem identification, namely the community's low income caused by the covid19 pandemic. The community still does not have enough knowledge or skills to help economic improvement or increase family income through UMKM. This article aims to describe community empowerment efforts in the economic sector through Ladu Arai Pinang UMKM in Lubuk Buaya, Padang City. Based on the results of family economic empowerment through UMKM Pastries or Ladu Arai Pinang Cakes, it can be concluded that from the overall results of the empowerment process, it can be said that Ladu Arai Pinang UMKM in empowering the community's economy, especially mothers are pretty capable of empowering their economy